EFFECT OF PLANTING MEDIA ON THE GROWTH OF Shorea pinanga Scheff. SEEDLINGS - Diana Prameswari; Hesti Lestari Tata (Indonesian Journal of Forestry Research, 2004)
Shoreapinanga Scheff.   is a major tropical plant species which has an important  economic  value not  only for timber,  but also as illipe nut  (called tengkawang  in local  name) production.   This species   is suggested   for  land  rehabilitation    and  forest  conservation.    In rehabilitation   action, S. pi11a11ga is usually   planted   on the poor  and degraded  area.   Application   of  chemical  fertilizer and compost  is used to increase  the survival  and growth  of  the  seedlings.  Excessive chemical fertilizer  input  to soil, however,  may cause  negative  effect on  soil,  plant  and  environment. Conversely,  compost  may improve soil porosity, soil aggregate,  water absorption   and soil fertility. The objective  of  the study  was  to examine  effect  of  planting  media  on growth  of  S. pinanga  seedlings. Complete  randomized  design has been arranged with 5 treatments,  e.g. soil mixed with husk  (at the proportion   of  1:1), soil mixed with acacia compost  (1:1),   soil mixed with charcoal of  rice husk (1:1)   and soil mixed with humic acid (1:1).    Another  treatment  was  soil alone  used as control.   The  result showed that  growth  of  both  stem  height   and  diameter,  and  index  of seedling  quality  were affected  significantly   by planting  media.    The mixture  of  soil and  acacia compost  (1 :1)  was the best  planting media for the growth  of S. pinanga seedlings,  which resulted in the growth  of height  (24.19   cm) and stem diameter  (0.246 cm).  Meanwhile, soil mixed with rice husk charcoal (1:1)  gave the best result to the index of  seedling quality (ISQ = 1.34)   and total dry weight (TOW=   15.93  g).